Advertisement

Here's f(x) again, in case you forgot:

f( x ) = x^2 + 3

Remember the blob game:

f( blob ) = ( blob )^2 + 3

So, for  f(g(x))... our blob is g(x)...

f( g( x ) ) = ( g( x ) )^2 + 3

There's more to the problem and we aren't finished, but I'm going to linger here for a bit because I know that this can get confusing if you jump in too quickly.

Let's look at another one...

Givenf( x ) = 5x - 3

Here's  f(blob):

f( blob ) = 5( blob ) - 3

Here's  f(g(x)):

f( g( x ) ) = 5( g( x ) ) - 3

One more:

Givenf( x ) = 7x^2 - x + 3


f( blob ) = 7( blob )^2 - ( blob) + 3
These ( ) will be REALLY important!

f( g( x ) ) = 7( g( x) )^2 - ( g( x ) ) + 3